Determinants of child malnutrition and morbidity in Ethiopia: a structural equation modeling approach - Warssamo, Birhanu Betela; Belay, Denekew Bitew; Chen, Ding-Geng (Frontiers in Pediatrics, 2025)
BackgroundChildhood malnutrition and morbidity remain significant public health challenges in Ethiopia, highlighting the need to assess the risk factors contributing to these issues for effective prevention and control strategies. Thus, this study aims to investigate the underlying risk factors by employing a structural equation model to analyze malnutrition as a mediator in the relationship between selected factors and morbidity.MethodsThe study utilized data from the 2016 Ethiopia Demographic and Health Survey and a sample of 8,560 under-five children were considered. The structural equation model was used to examine the association between child malnutrition, morbidity, and potential risk factors. The structural equation model makes it possible to analyze malnutrition as a mediator of the association between selected risk factors and morbidity.ResultsOut of the 8,560 sampled children, 12.80% were wasted, 34.75% were stunted, 23.91% were underweight, 13.9% had fever, 11.2% had diarrhea, and 59.7% had anemia. Birth interval, wealth index household, place of delivery, size of child at birth, number of children, and socioeconomic condition had a significant direct effect on childhood malnutrition and morbidity. The time to get water, toilet facility, and child is a twin variables had direct effects on childhood malnutrition and had no significant direct effects on childhood morbidity. Time to get water, birth interval, toilet facility, wealth index of household, child is a twin, place of delivery, size of child, and number of children exhibited an indirect effect on morbidity through malnutrition.ConclusionsThe study revealed that there was a high prevalence of malnutrition and morbidity among under-five children in Ethiopia. Time to get water in min, place of delivery, size of child, and number of children showed a significant indirect and total effect on morbidity through malnutrition and socioeconomic conditions showed a significant total effect on morbidity via malnutrition. Implementing and extending programs such as community-based nutrition interventions for early childhood is critical, as early malnutrition showed long-term effects on growth and immunity, particularly in the regions of Affar, Dire Dawa, Gambela, Harari, Amhara, and Somali.